Analisis Faktor – Faktor Yang Menentukan Minat Para Angel Investor Dalam Berinvestasi Untuk Startup Perusahaan - Anindhita, Yusi (Universitas Mercu Buana, 2023)
The development of startups in Indonesia in 2022 in Indonesia is increasing. A startup company is a company in the early stages of operation. Most start-up companies are looking for new and repeat business models. The risk of startup companies is higher than companies that have stable profits and market share. Therefore it is important to analyze the potential and threats in the sector. One of the key success factors for this startup is finding sufficient financial resources to develop the idea, especially in the non-revenue startup phase. Therefore startups must seek external financial sources, one of which is funding from angel investors. The purpose of this research is to get the most dominant factors that influence angel investors in determining the choice of investing in food and beverage startups. The method used is the Analytic Hierarchy Process (AHP). Factors that influence angel investors in investing in startup companies are product and service factors, market factors, character factors and the background of the founders as well as financial condition factors. The highest value of the relative factor is 1.625442 on the company's reputation sub-factor on product and service factors. The results of the interviews show that the activities and actions of the company's management in the past were evaluated regularly and the results of the company's products were satisfactory, good public trust, and the company's financial performance was also positive.